Historia Skulbaszewskiego. Przyczynek do badań nad bezsilnością prawa - Kutkowski, Arkadiusz (Komunizm: System - Ludzie - Dokumentacja, 2023)
The following article outlines attempts to prosecute Antoni Skulbaszewski, a chief military prosecutor in 1948–1950, later a long-term deputy head of the Main Information Board of the Polish Army, and in the public opinion a Stalinist felon. Such attempts were made both in the times of the Polish People’s Republic and after the political breakthrough of 1989–1990 to no avail. The author tries to discover why these efforts were futile and concludes that it resulted from political decisions made by Władysław Gomułka and his accomplices, who right after the “breakthrough” of 1956 decided not to prosecute Soviet officers. A further contributor was a peculiar “impossibilism” of the Ukrainian prosecutor’s office, which after the collapse of the USSR and gaining independence by Ukraine, did not consent to prosecute Skulbaszewski, who was already a Ukrainian citizen. In addition, the article sheds some light on little-known facts from life of the former chief military prosecutorand raises a question whether they can be viewed from the angle of H. Arendt’s well-known thesis of “banality” in totalitarian systems.